The Effectiveness of SrVER-Based Learning Modules Integrated with Augmented Reality on Students Self-Efficacy in Excretory System Topics - Resta Aulia Lestari; Baiq Sri Handayani; Marosa Robiatul Adawiyah; Tri Ayu Lestari (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram. Jurnal Pijar MIPA colaborates with Perkumpulan Pendidik IPA Indonesia Wilayah Nusa Tenggara Barat, 2026)
Biology learning requires students to have self-efficacy, namely, confidence in their abilities to solve learning problems and complete certain tasks. SrVER is a learning model that emphasizes a visual learning style, which adapts the main principles in the teaching and learning process, namely Screening, Visualization, Elaboration, and Reflection. The SrVER model can be considered one approach with the potential to improve student self-efficacy. The purpose of this study was to determine the effectiveness of SrVER-based learning modules integrated with Augmented Reality (AR) on student self-efficacy in excretory system material at SMAN 2 Mataram. This study used a quantitative experimental method with a non-equivalent control group design and purposive sampling. The experimental group was given treatment, namely the use of the AR-integrated SrVER learning module, while the control class, the learning was as usual for teachers. Data collection in this study was carried out by distributing questionnaires to students, totaling 28 questions. Data were analyzed using the Mann–Whitney U test because the data were not normally distributed. The results of the study obtained an Asymp. Sig. (2-tailed) value of 0.003, which indicates that the value is <0.05, so that Ha is accepted and Ho is rejected, so that it can be interpreted that there is an effectiveness of the use of the SrVER learning module integrated with augmented reality on student self-ability in the excretory system material for class XI of SMAN 2 Mataram. These findings indicate that integrating SrVER and AR can support more interactive and meaningful biology learning.